Health Impacts of Biophilic Design from a Multisensory Interaction Perspective: Empirical Evidence, Research Designs, and Future Directions - Jie Yin; Haoyue Zhu; Jing Yuan (Land, 2024)
Biophilic design introduces a variety of sensory elements into the built environment, incorporating a natural experience into daily life. From the environmental psychology aspect, the effects of multisensory stimulus are not a result of simply adding the effects of uni-sensory stimuli, and the interactive effects among sensory approaches need to be considered. With the demand for promoting health and well-being, increasing numbers of studies began to investigate sensory systems other than just the visual cue of the biophilic design. This review focuses on the multisensory effect of biophilic design on human psychological and physiological responses as well as cognitive function. We summarized empirical evidence of the interactions between two and three sensory modalities from existing research. In addition, we systematically summarized the key methods and technologies used in experimental studies that explore the health benefits of biophilic design in terms of study types and population, environmental exposure simulation, health benefit measurement, and experimental process design. We finally identified some knowledge gaps in and future directions for biophilic design studies from the multisensory interaction perspective. The experimental design of quantifying the effects of multisensory interaction and its lasting effects are the focus of future research.